Adolescent human immunodeficiency virus self-management: Needs of adolescents in the Eastern Cape - Leone Adams; Talitha Crowley (AOSIS, 2021)
Background: Human immunodeficiency virus (HIV) is a chronic illness and adolescents living with HIV (ALHIV) need the support of the whole family to self-manage (handle, direct and control) their chronic illness. Little is known about self-management amongst ALHIV in the context of the Eastern Cape, South Africa. Aim: This study explored the self-management needs of ALHIV in the Nelson Mandela Bay area of the Eastern Cape to make recommendations that can be used in further research to develop a programme to support adolescents with self-management. Setting: The study was conducted at two primary healthcare clinics in the Nelson Mandela Bay area of the Eastern Cape. Methods: A qualitative descriptive design was applied. Thirteen adolescents between the age of 14 and 19 years were interviewed. The data were collected through individual interviews. Data analysis was done using the six steps described by Creswell. Results: Adolescents living with HIV have limited knowledge and understanding about HIV and sexual reproductive health. Some ALHIV lack self-regulation skills related to decisions about disclosure, managing stigma and emotions, taking treatment, effective communication and setting goals. Human immunodeficiency virus services were not adolescent-friendly, with long queues and no dedicated services for adolescents. Family and friends were a key self-management resource for ALHIV. Conclusion: Adolescents living with HIV have several self-management needs in the domains of knowledge and beliefs, self-regulation skills and abilities, and self-management resources. Healthcare workers should support adolescents and their caregivers to acquire self-management skills as this may lead to better treatment and health outcomes.